Sweet taste brings happiness, but happiness does not taste sweet: the unidirectionality of taste-emotion metaphoric association. Issue 3 (3rd April 2022) - Zhou, Yanyun; Tse, Chi-Shing
ABSTRACT: According to the Conceptual Metaphor Theory, abstract concepts can be understood in terms of concrete concepts, but not vice versa, suggesting the unidirectionality of metaphoric association. In the current four experiments (valid N = 541), we examined the directionality of taste-emotion metaphoric association. To test the taste-to-emotion metaphoric association, we had participants rate on pleasantness after consuming a chocolate or rate their change in emotion using different scales before and after consuming a chocolate. To examine the emotion-to-taste metaphoric association, we induced participants' emotion via watching film clips or retrieving autobiographical memory and asked them to rate the sweetness and bitterness after consuming a chocolate. With a more optimal design, results showed that sweet chocolates increased positive emotion and reduced negative emotion, whereas bitter chocolates increased negative emotion and reduced positive emotion. In contrast, induced emotion did not influence participants' perception of chocolate taste. Other possible mechanisms are discussed.